第58次日本南極地域観測隊気象部門報告2017 - 水野, 太治; ミズノ, タイジ; 重岡, 裕海; シゲオカ, ヒロウミ; 小野, 文睦; オノ, フミチカ; 森, 陽樹; モリ, ヨウキ; 梅澤, 研太; ウメザワ, ゲンタ; Mizuno, Taiji; Shigeoka, Hiroumi; et al. (国立極地研究所, 2020)
この報告は第58 次日本南極地域観測隊気象部門が，2017 年2 月1 日～2018 年1 月31 日まで昭和基地において行った気象観測結果をまとめたものである．観測方法，測器，統計方法等は第57 次隊とほぼ同様である．越冬期間中の特記事項としては，次のものが挙げられる． 1） 月平均気温は6 月と8 月に平年を下回ったが，その他の月は平年並みか平年よ り高く経過した． 2） 2017 年12 月23 日から25 日にかけて昭和基地の北の海上を通過した低気圧の 影響で，5 年ぶりに雨が観測された． 3） 2017 年の南極オゾンホールの面積は，8 月中旬以降，過去10 年間の平均値よ り小さく，9 月中旬・下旬には過去10 年間の最小値より小さく推移し，最大 面積は過去29 年間で最小となった． This report describes the results of meteorological observations at Syowa Station from February 1st, 2017 to January 31st, 2018, carried out by the Meteorological Observation Team of the 58th Japanese Antarctic Research Expedition (JARE-58). The observation methods, instruments, and statistical methods used by JARE-58 were almost the same as those used by the JARE-57 observation team. Remarkable weather phenomena observed during the period of JARE-58 are as follows. 1) The average temperature of the month fell below normal in June and August, but the other months were either the same as normal or higher than normal. 2) The rain was observed for the first time in five years, under the influence of a cyclone passing through the sea north of Syowa Station from December 23 to 25. 3) The area of the Antarctic ozone hole in 2017 was smaller than the average for the past ten years since mid-August. In mid and late September, it remained smaller than the minimum for the past ten years. The largest area was the smallest in the past 29 years. departmental bulletin paper